Identificação de uma nova mutação no gene TCAP/Teletonina numa família portuguesa com miocardiopatia hipertrófica - Toste, Alexandra (2020)
Introduction and objectives: Hypertrophic cardiomyopathy (HCM) is a genetically and phenotypically heterogeneous disease; there is still a large proportion of patients with no identified disease-causing mutation. Although the majority of mutations are found in the MYH7 and MYBPC3 genes, mutations in Z-disk-associated proteins have also been linked to HCM. Methods: We assessed a small family with HCM based on family history, physical examination, 12-lead ECG, echocardiogram and magnetic resonance imaging. After exclusion of mutations in eleven HCM disease genes, we performed direct sequencing of the TCAP gene encoding the Z-disk protein titin-cap (also known as telethonin). Results: We present a novel TCAP mutation in a small family affected by HCM. The identified p.C57W mutation showed a very low population frequency, as well as high conservation across species. All of the bioinformatic prediction tools used considered this mutation to be damaging/deleterious. Family members were screened for this new mutation and a co-segregation pattern was detected. Both affected members of this family presented with late-onset HCM, moderate asymmetric left ventricular hypertrophy, atrial fibrillation and heart failure with preserved ejection fraction and low risk of sudden cardiac death. Conclusions: We present evidence supporting the classification of the TCAP p.C57W mutation, encoding the Z-disk protein titin-cap/telethonin as a new likely pathogenic variant of hypertrophic cardiomyopathy, with a specific phenotype in the family under analysis.